Evaluation of Thyroid Hormone Levels in Women after Total Thyroidectomy for Thyroid Cancer - Dakhil, Kareema A.; Dikain, Kawther Hussein; Hassan, Athraa Kadhim; Humadde, Hadeel Satar (Central Asian Journal of Medical and Natural Science, 2025)
Thyroid cancer often necessitates total thyroidectomy, a procedure that significantly alters thyroid hormone levels and can lead to hypothyroidism if not properly managed.This study aimed to evaluate thyroid hormone levels in patients who have undergone total thyroidectomy for thyroid cancer, compared to healthy individuals, to understand the physiological effects of the surgery. A total of 100 participants aged 25 to 45 from Dhi Qar Province were enrolled and evenly divided into two groups: patients who had undergone total thyroidectomy (Group A) and healthy controls. After a 12-hour fast, blood samples were collected, and serum levels of T3, T4, and TSH were measured using ELISA kits. Statistical analysis was performed using ANOVA and the LSD test, with significance set at P < 0.05. Group A showed significantly lower levels of T3 (0.47 ± 0.10 ng/ml) and T4 (88.11 ± 8.73 nmol/l) compared to the control group (T3: 1.23 ± 0.27 ng/ml; T4: 115.69 ± 15.75 nmol/l). Conversely, TSH levels were markedly higher in Group A (8.27 ± 1.03 µIU/ml) than in the control group, indicating postoperative hypothyroidism. These differences were statistically significant (P < 0.05).